2015
DOI: 10.1093/jpepsy/jsv006
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Pediatrics Feeding Assessment Scale in Young Children With Autism Spectrum Disorder: Psychometrics and Associations With Child and Parent Variables

Abstract: These results provide evidence supporting the use of the identified BPFAS three-factor model for samples of young children with ASD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(39 citation statements)
references
References 45 publications
2
32
0
5
Order By: Relevance
“…Seeking for alternatives for their children to eat, besides possible implications on the narrower variety of foods, family's dinnertime routine can also be affected. Analyzing BPFA in ASD participants, according to Allen et al (2015), the food acceptance category showed that fruits and vegetables were fewer consumed, as also described in the literature (Evans et al, 2012; Hubbard et al, 2014; Johnson et al, 2014). On the other hand, most ASD participants enjoy eating, and eat starches regularly.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Seeking for alternatives for their children to eat, besides possible implications on the narrower variety of foods, family's dinnertime routine can also be affected. Analyzing BPFA in ASD participants, according to Allen et al (2015), the food acceptance category showed that fruits and vegetables were fewer consumed, as also described in the literature (Evans et al, 2012; Hubbard et al, 2014; Johnson et al, 2014). On the other hand, most ASD participants enjoy eating, and eat starches regularly.…”
Section: Discussionsupporting
confidence: 55%
“…In addition, a recent study proposed a three factors model (food acceptance, medical/oral motor and mealtime behavior) to analyze BPFA as a methodology for children with ASD (Allen et al, 2015). Therefore, we used this model to describe feeding behavior in ASD children.…”
Section: Methodsmentioning
confidence: 99%
“…Satisfaction is linked very strongly with security, trust, and confidence and it also influenced by personal opinions, beliefs, expectations, and experiences (Condelius & Andersson, 2015). Family satisfaction is a protective factor in children with eating disorders (Allen et al, 2014).…”
Section: Ingestive / Eliminative Subsystemmentioning
confidence: 99%
“…The eating disorder in infants and toddlers is caused by several factors, including: genetic and biological factor, environmental and sociocultural influences, and psychological stress (Campbell & Peebles, 2014;De Luca & Napoletani, 2015), mother and family factor (Allen et al, 2014), and dysfunctional interaction between mother and child (Goulding et al, 2014;Gueron-Sela, Atzaba-Poria, Meiri, & Yerushalmi, 2011;Kröller & Warschburger, 2009;Sacrato et al, 2010;Squires, Lalanne, Murday, Simoglou, & Vaivre-Douret, 2014). The prevalence of affectionate tension between parents and child is 13 -82%, depending on the risk factor in the family such as negligence or maltreatment to the child (Skovgaard Vaever, Smith-Nielsen, & Lange, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…evelopment of new scales as assessment tools of swallowing and eating behaviors and dysphagia for children is increasing [1][2][3][4]. Nowadays, due to appropriate therapeutic techniques, more children and adults are being survived from medical accidents.…”
Section: Introductionmentioning
confidence: 99%